Reduction in Severance Pay as a Result of the Implementation of the Job Creation Law in Electronics Companies in the Cibitung Industrial Area - Hermawan, Hendra; Setiawan, Ichwan (Neolectura, 2024)
This research aims to analyze the impact of the implementation of the Omnibus Law (Law No. 11 of 2020) on severance pay amounts in electronics companies in the Cibitung Industrial Area. The Job Creation Law, known as the Omnibus Law, has brought significant changes in various aspects of employment, including regulations regarding severance pay for employees affected by termination of employment. Through qualitative and quantitative approaches, this research analyzes the regulatory changes concerning severance pay, measures the economic impact of severance pay reduction on workers, and explores the perceptions of workers and employers regarding these policy changes. Data were collected through document studies, surveys, and interviews with workers, labor unions, and employers, as well as secondary data analysis from labor reports and statistics.The research results show that the implementation of the Omnibus Law has caused a significant reduction in the severance pay amounts received by employees. Factors influencing this reduction include changes in the severance pay calculation formula and the imposition of a maximum severance pay limit. The impact of this reduction in severance pay is felt significantly by employees, particularly in terms of their economic well-being post-termination.This research suggests the need for more intensive socialization of the new regulations and the enhancement of protection mechanisms for affected employees. This research aims to analyze the impact of the implementation of the Omnibus Law (Law No. 11 of 2020) on severance pay amounts in electronics companies in the Cibitung Industrial Area. The Job Creation Law, known as the Omnibus Law, has brought significant changes in various aspects of employment, including regulations regarding severance pay for employees affected by termination of employment. Through qualitative and quantitative approaches, this research analyzes the regulatory changes concerning severance pay, measures the economic impact of severance pay reduction on workers, and explores the perceptions of workers and employers regarding these policy changes. Data were collected through document studies, surveys, and interviews with workers, labor unions, and employers, as well as secondary data analysis from labor reports and statistics.The research results show that the implementation of the Omnibus Law has caused a significant reduction in the severance pay amounts received by employees. Factors influencing this reduction include changes in the severance pay calculation formula and the imposition of a maximum severance pay limit. The impact of this reduction in severance pay is felt significantly by employees, particularly in terms of their economic well-being post-termination.This research suggests the need for more intensive socialization of the new regulations and the enhancement of protection mechanisms for affected employees.